THE INFLUENCE OF SOCIAL RESPONSIBILITY FOR BUSINESSES ON THE GROWTH OF LOCAL COMMUNITIES - Kansilembo Aliamutu; Kerry Lee Gurr (CV. RADJA PUBLIKA, 2024)
In recent years, as the concept of social responsibility has been ingrained in our language, commercial companies have faced increasing demands to take accountability for the environments in which they operate. The aim of this research is to assess the influence of social responsibility for businesses on the growth of local communities. The quantitative approach was used to gather the primary data. In the Northern part of KwaZulu-Natal (KZN) province, certain locations of Richards Bay were the site of data collection. There were 129 participants in the sample who were community members. The research's dependability data was determined to be significant in 0.782. The findings show that most participants think they acquire several advantages from doing business with a local business. The results also show that investments in social technological advances, building capacity, contracting and business possibilities, and employment creation are among the advantages. The exploratory and quantitative character of the research places limitations on its findings. It is advisable to use caution when making generalisations and to do more research with bigger samples and to consider the perspectives of other provinces.